Operational Characteristics of Research and Test Benches and Installations with Heavy Liquid Metal Heat Carriers - T. A. Bokova; A. G. Meluzov; N. S. Volkov; A. R. Marov; A. V. Lviv (Приборы и методы измерений)
The topic of research stands on heavy liquid metal coolants is currently undergoing a rebirth. Experimental stands have been built, for example, LILLA SCK CEN (Center for Nuclear Research in Belgium, Mol). This is one of the most famous stands that uses heavy liquid metal heat carriers. But a sufficiently complete description of the equipment line-up and the application of specific solutions for monitoring and maintaining the operability of the stands at the heavy liquid metal coolants is not published in the open press. Most likely, this is due to the specifics of research where there is a sufficient amount of secrecy. The aim of the work was to conduct a comprehensive review of various equipment use in this field. This will make it possible to plan more efficient composition of new research stands at heavy liquid metal coolants and avoid unnecessary mistakes when operating them. Heavy liquid metal heat carriers of nuclear power plants such as lead, eutectic lead-bismuth alloy, lead-lithium, gallium alloys differ significantly in their physicochemical properties from traditional and well-studied, widely used water, sodium, as well as liquid salt heat carriers, potassium, gases (helium, etc.).